Alison Blesser: capstone - Blesser, Alison, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work is created through daily inspirations, be they pop culture, my family, friends, everyday connections, or how I interpret the world around me. I like to create my work digitally, but I often base my work on first interpretations through sketches or physical manipulation of materials. I've always been an artist that enjoys simplicity over complexity, but have the ability to find both in my work when appropriate. The art I create is inspired by my nerdy nature to read books, watch movies, and discuss with family and friends the unique and finite details that I enjoy - and want to create art about. The excited behind the tale of The Odyssey, the complexity of the world created by J. R. R. Tolkien (Middle Earth), or the characters I have fallen in love with reading books over my lifetime, lets me delve into detail about things I love and create art that I am proud of. Whether I'm creating branding material, posters, or layouts - I always strive to find the balance of bringing forward the emotion and message behind the client or topic to my art in a way that accurately represents what I am trying to portray in my creations.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.